1973
DOI: 10.1111/j.1469-8986.1973.tb00807.x
|View full text |Cite
|
Sign up to set email alerts
|

Race Differences and Experimenter Race Effect in Galvanic Skin Response

Abstract: The present study was designed to ascertain whether racial differences exist in the several components of the skin resistance response and to assess the importance of the role of the experimenter's race in determining the subject's responsiveness. Basal measures, GSR magnitude, and spontaneous GSR activity of 12 Negro and 12 Caucasian Ss were recorded by 2 Negro and 2 Caucasian experimental assistants matched for age, physical stature, and dress. Following a 15 min resting phase, all Ss received 14 1‐sec burst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Johnson and Corah (1963) found reliably higher base levels of skin resistance in African-Americans than in Caucasians, and Bernstein (1965) reported the same for skin impedance levels, 102 both in schizophrenic patients and normal controls, independent from the examiner being of either ethnic group. An increased SRL in African-Americans which is independent from the experimenter's skin color was also confirmed by Fisher and Kotses (1973). 103 No differences in NS.SRR freq.…”
Section: Ethnic Differences and Heritabilitymentioning
confidence: 75%
“…Johnson and Corah (1963) found reliably higher base levels of skin resistance in African-Americans than in Caucasians, and Bernstein (1965) reported the same for skin impedance levels, 102 both in schizophrenic patients and normal controls, independent from the examiner being of either ethnic group. An increased SRL in African-Americans which is independent from the experimenter's skin color was also confirmed by Fisher and Kotses (1973). 103 No differences in NS.SRR freq.…”
Section: Ethnic Differences and Heritabilitymentioning
confidence: 75%
“…That is to say, ethnicity or race may appear to affect SC because of group differences in skin color. For example, researchers have reported that African-American people have lower SC levels than White people (Boucsein, 1992;Fisher & Kotses, 1973;Johnson & Corah, 1963) and that SC levels of Native Americans fall midway between those of White and African-American people (Korol & Kane, 1978). These reports suggest that darkness of skin color, rather than race or ethnicity, influences SC.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Because blacks scored significantly higher than whites on the upset factor (see Table 5), it appears that blacks could be disposed toward becoming more aroused than whites in testlike settings. This observation has received some independent physiological confirmation by Fisher and Kotses (1973). A disproportionate number of blacks at the higher, overly stressed levels of arousal could be yet another phenomenon contributing to interracial differences in task performance and mean IQ.…”
Section: Discussionmentioning
confidence: 88%